Pengaruh Penerapan Model Kooperatif Tipe TGT Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP Muhammadiyah Limbung - Farhanah Rahmah; Wahyuddin Wahyuddin; Nursakiah Nursakiah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this study was to determine the effect of the application of the Teams Games Tournament (TGT) cooperative learning on the mathematics learning outcomes of students in class VIII SMP Muhammadiyah Limbung. This type of research is pre-experimental with the research design used is One Group Pretest-Posttest Design. The sample in this study was class VIII.1 with a total of 30 students. The sampling technique used is simple random sampling. The instruments used to collect data were student mathematics learning outcomes tests (pretest and posttest), student activity observation sheets, and student response questionnaires. The data analysis of this research is descriptive statistical analysis and inferential statistical analysis. Based on the results of research and discussion, it is concluded that: (1) The students' mathematics learning outcomes have increased with the average score of students' mathematics learning outcomes after the application is 84.33 and the results of the n-gain test are  obtained  or so that the n-gain value is more than 0.3. (2) The average percentage of student activity is 82.65%, so student activity reaches the active criteria and (3) Student responses are positive where the average percentage is 83.11%. Thus, the application of the Teams Games Tournaments (TGT) cooperative learning has an effect on the mathematics learning outcomes of students in class VIII SMP Muhammadiyah Limbung.